Evaluasi Kelayakan Usaha Katering Rumahan Ditinjau dari Aspek Keuangan - Raihan Ramadhan Aziz (CV. Aksara Global Akademia, 2024)
Financial aspects are needed to assess whether or not a business is feasible to continue because the amount of income obtained from sales is the key to the success of a business. The purpose of this research is to evaluate the feasibility of Kokom Katering business from the financial aspect. The research method uses quantitative descriptive with direct data collection in the field, with the research location at Kokom Katering located in Cikampek with the research time in June 2024. From the results of the research, the Kokom Katering business received total revenue in May 2024 of Rp. 16,875,000 with production costs of Rp. 12,150,000 so that the profit obtained was Rp. 4,725,000 as of May 2024, so it can be concluded that the Kokom Katering business is profitable.